Exploring High School Students’ Perception of Mobile-Cipta Puisi (MCP) Application - Kartini, Ari; Sunendar, Dadang; Sumiyadi, S; Yulianeta, Y; Zuhro, Putri Fatimatuz (CV Sinergi Ilmu dan Publikasi, 2025)
This study aims to explore students' perceptions of Mobile-Cipta Puisi (MCP), a digital learning application designed to foster creativity and enhance the learning experience in poetry writing. This study employed a descriptive quantitative approach utilizing a survey design. Data were collected using a Likert-scale questionnaire covering two main aspects: students’ responses to the application's format and usefulness, and their reactions, including interest and self-confidence. A total of 126 tenth-grade high school students from five schools in Garut Regency participated as respondents. The collected data were analyzed descriptively using descriptive statistical methods. The results indicate a notably positive reception of MCP, with an average score of 83% across both measured aspects. Features such as relaxation music, the ability to save and share poetry, and access to inspirational poems were particularly appreciated for making the poetry-writing process both enjoyable and accessible. A novel contribution of this research lies in the development and testing of MCP as a poetic learning tool that not only offers a digital writing medium but also integrates emotional and collaborative support features elements that are rarely found in similar applications within the context of Indonesian literary education.